PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Zakia Az’zahra Qurota’aini; Deviyanti Pangestu; Siti Nuraini; Ari Sofia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem identified in this research was the low critical thinking skills of students in Pancasila Education at SD Negeri 1 Karang Anyar. This condition was influenced by a lack of variety in learning models, which resulted in students being less active during the learning process. This study aimed to determine the effect of the Mind Mapping learning model on the critical thinking skills of fourth-grade students during the 2025/2026 academic year. The research population consisted of all 85 fourth-grade students. The sample was selected using a purposive sampling technique based on class characteristic suitability, involving 58 students: Class IVA as the control group and Class IVC as the experimental group. This study employed a quantitative approach with an experimental method, specifically a nonequivalent control group design. The research instruments comprised 15 essay questions and observation sheets to monitor the learning implementation. Based on the hypothesis testing using the Paired Sample t-Test, the results showed a Sig. (2-tailed) value of 0.000 < 0.05. Consequently, it was concluded that the implementation of the Mind Mapping learning model had a significant effect on the students' critical thinking skills in Pancasila Education at SD Negeri 1 Karang Anyar for the 2025/2026 academic year.